Gamma Knife Radiosurgery (GKRS) for Patients with Prolactinomas: Long-Term Results From a Single-Center Experience - Li, Yanli (Med Sci Monit, 2020)
BACKGROUND: The aim of this study was to review outcomes of gamma knife radiosurgery (GKRS) for prolactinoma and report our experience with it. MATERIAL/METHODS: We reviewed the patient database in our center and identified 24 patients with prolactinoma who underwent GKRS from 1993 to 2016. Complete endocrine, clinical, and radiological data were available on these individuals before and after GKRS. RESULTS: Data from 5 males and 19 females with a median age of 30.5 years (range, 18.1 to 51.1) were reviewed. The median follow-up was 109.3 months (range, 23.2–269.3). The median margin dose of GKRS was 15 Gy (range, 10.5 to 23.6). In total, prolactin (PRL) normalization after GKRS was achieved in 66.7% of patients. Endocrine remission (normal PRL levels after discontinuation of dopamine agonists) was achieved in 10 patients (41.7%), and endocrine control (normal PRL levels while taking dopamine agonists) was achieved in 6 patients (25.0%). All of the patients showed tumor control. New-onset hypopituitarism post-GKRS occurred in 4 patients (16.7%). No new visual dysfunction or cranial nerve dysfunction were observed after GKRS. CONCLUSIONS: For treatment of prolactinomas, GKRS may provide relatively high rates of endocrine remission and tumor control, as well as a low rate of new-onset hypopituitarism. GKRS may be an effective and safe treatment for prolactinomas.